Analisis Pengelolaan dana Investasi Asuransi Jiwa Syariah (Studi Kasus PT. Asuransi Sunlife Cabang Medan) - Mandani, Putih; Rahmani, Nur Ahmadi Bi; Nurwani, Nurwani (LPPM Universitas Labuhanbatu, 2023)
This study aims to determine the management of sharia life insurance investment funds and find out the constraints that occur in the management of sharia life insurance investment funds at PT. Sun Life Medan Branch. The research method used in this study is a descriptive qualitative approach method. Data collection techniques in the form of interviews and using primary data obtained directly from PT. Sun Life Medan Branch. The subjects in this study were employees and customers at PT. Sun Life Medan Branch and the object of this study is the management of investment funds at PT. Sun Life Medan Branch. Based on the results of research on the management of sharia life insurance investment funds at PT. Sun Life Medan Branch is in accordance with sharia principles which are free from elements of gharar, maisyr and usury which refers to the fatwas of the National Sharia Council-Indonesian Ulema Council (DSN-MUI) and regulations stipulated by the Financial Services Authority (OJK) as well as on fund management transparent in accordance with Islamic law. Then in managing the funds there were no obstacles, but the obstacles existed when the emergence of Covid-19 in Indonesia where the financial dampening in investing tabarru funds decreased. Companies must pay customer claims because customer claims have increased so that expenses will increase.